Fragile Political Coalitions: Negotiating Race and Class in the Opt-Out Movement. Issue 5 (May 2021) - Wilson, Terri S.; Contreras, Ana; Hastings, Matthew
Background/Context: Recent movements to "opt out" of state assessments have brought together a broad and diverse group of activists. While many activists foreground concerns of equity and justice, opting out has been concentrated in affluent suburban communities. These differences highlight questions of power and privilege within the movement: in what ways is opting out more acceptable—and politically persuasive—because it has primarily been driven by affluent white communities? How has the opt-out movement incorporated—or elided—the voices, interests, and perspectives of communities of color? Purpose/Objective/Research Question/Focus of Study: To explore these questions, this study focuses on how opt-out activists describe the aims of their movement and how they negotiated tensions related to race, power, and privilege in education activism. How might we understand the potential coalitions and fault lines within the diverse opt-out movement? Research Design: Drawing on the insights of critical discourse analysis (CDA), we analyze presentations and interactions from a national conference on opting out held in 2016. We focus on publicly accessible video recordings of major sessions (keynotes and panels) to describe how activists describe the aims, strategies, and potential compromises of the opt-out movement. We also draw on several secondary sources of data (social media, webinars, blog posts, and other publications from opt-out leaders) to add context to our analysis. Data Collection and Analysis: We use concepts in social movement theory, including movement identity and "splintering, " to frame some emerging fissures among opt-out activists, particularly across lines of class, race, and power. We organize our findings into three interrelated themes, describing how activists framed and negotiated the aims of opting out, often across lines of race and class, and worked to build solidarity amid moments of dissent. Conclusions/Recommendations: While politically successful in some respects, the anti-testing coalition remains fragile and divided, leaving its goals for equity-oriented reform uncertain. Certain longstanding issues (the inclusion of communities of color) and particular policy decisions (collaborating with local union and civil rights chapters) have contributed to fractures in the movement. However, activists may capitalize on dissent to expand the boundaries of their movement and build more diverse and expansive networks.